Intussusception in Neonates: Clinical Characteristics of Eight Cases in a Single Center - Yong-gi Ahn; Gina Lim; Eun Ha Hwang; Ki Won Oh; Min Jeng Cho (Korean Society of Neonatology, 2021)
Purpose Intussusception is the most common cause of bowel obstruction in children; however, it is rarely diagnosed in newborn infants. This study aimed to describe the clinical features of intussusception in newborn infants. Methods Medical records of eight patients diagnosed with intussusception during the newborn period at Ulsan University Hospital between March 2007 and March 2020 were retrospectively reviewed. Results Among the eight cases, two occurred in the intrauterine period and six occurred in the postnatal period. Intrauterine intussusception presented with symptoms of bowel obstruction within 1 to 2 days after birth, and ileal atresia was diagnosed simultaneously through exploratory laparotomy. All the postnatal patients were extremely low birth weight infants (median gestational age and birth weight: 25+6 weeks and 745 g, respectively). Four cases were diagnosed preoperatively using abdominal ultrasonography. One patient was diagnosed by exploratory laparotomy because the clinical symptoms were nonspecific and difficult to differentiate from those of necrotizing enterocolitis, a more prevalent complication in preterm infants. The site of intussusception in all six patients was the small bowel. Meckel's diverticulum (one case) and meconium obstruction (two cases) were found to be the lead point. Conclusion Neonatal intussusception tends to show different clinical features according to its period of occurrence. Intussusception, especially in preterm infants, has nonspecific clinical features; therefore, clinicians should always be cautious of this disease for its early diagnosis.